Upaya Menjadi Wirausaha Mandiri Pada Mahasiswa Disabilitas Melalui Pendampingan - Neviyani, Neviyani; Redjeki, Sri; Musthofa, Danis Nurul; Cahyono, Arie Eko (Education Journal : Journal Educational Research and Development, 2024)
PGRI Argopuro University Jember is a university with a vision of Quality Higher Education and National Competitiveness Based on Science and Technology in the fields of Local Wisdom, Entrepreneurship and Disability in 2030. The UNIPAR Jember Disability Study and Service Center provides assistance to students with disabilities as evidence of an inclusive education environment. By assisting students with disabilities, they are more courageous to start their own business, which helps them have sufficient human capital after graduating from school. This type of research is qualitative with data collection methods in the form of observation, documentation, and interviews This research was conducted qualitatively using a descriptive approach. The results of the research showed that the mentoring went well and the target fulfillment was in accordance with the steps of the mentoring activities that had been set. Participants already have entrepreneurial planning that will be followed up immediately. The business system management has been prepared in the form of work program instructions that can be used as a reference during the course of the business.